PENGARUH GAME BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR MATERI MAGNET, LISTRIK DAN TEKNOLOGI BAGI KEHIDUPAN PESERTA DIDIK KELAS V SD NEGERI 13 CURIO - Alief Muhammad; Dian Firdiani; Hasan; Muhammad Idham Khaliq; Fuad Danindra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes of fifth-grade students in Science and Social Studies (IPAS) at SD Negeri 13 Curio. Teacher-centered learning and the lack of innovative learning models and media have caused students to be less active during the learning process. This study aimed to determine the effect of Game Based Learning assisted by audio-visual media on students' learning outcomes in magnetism, electricity, and technology for life topics. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 21 students selected through saturated sampling techniques. Data were collected through pretests and posttests and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed that the mean pretest score was 61.90 and increased to 91.43 in the posttest. The Wilcoxon test yielded a significance value of 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, Game Based Learning assisted by audio-visual media had a positive and significant effect on students' IPAS learning outcomes.